2005
DOI: 10.1111/j.1745-4549.2005.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical and Microbial Changes in Shredded Sweet Potatoes+

Abstract: With the increasing demand for freshly cut vegetables, a substantial potential exists in developing minimally processed sweet potato products. This study was undertaken to determine the effects of semipermeable polymeric materials and modified atmosphere packaging (MAP) on quality changes and microbial growth in shredded sweet potatoes under refrigerated storage. Shredded sweet potatoes from two major commercial cultivars (Beauregard and Hernandez) were packed in low and medium O 2 permeability bags and flus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 31 publications
(73 reference statements)
2
28
0
Order By: Relevance
“…2). McConnell et al (2005) working with mashed sweet potatoes multilayer polyolefin bags packed, with an average permeability of O 2 and MAP, found decreases of 11% to 15% in the ascorbic acid content after 14 days at 4°C. In six cultivars of stripped potatoes packed in MAP, on the sixth day of storage at 4°C, Tudela et al (2002) reported a loss between 14% and 34% and it was different when product was stored in contact with air.…”
Section: Ascorbic Acidmentioning
confidence: 98%
See 2 more Smart Citations
“…2). McConnell et al (2005) working with mashed sweet potatoes multilayer polyolefin bags packed, with an average permeability of O 2 and MAP, found decreases of 11% to 15% in the ascorbic acid content after 14 days at 4°C. In six cultivars of stripped potatoes packed in MAP, on the sixth day of storage at 4°C, Tudela et al (2002) reported a loss between 14% and 34% and it was different when product was stored in contact with air.…”
Section: Ascorbic Acidmentioning
confidence: 98%
“…According to McConnell et al (2005), low luminosity or brightness values (L*) would indicate a greater degree of browning in cut vegetables. In experiences done in mashed sweet packed potatoes and stored at refrigeration temperatures, they did not detect changes in the L* value.…”
Section: Superficial Colormentioning
confidence: 99%
See 1 more Smart Citation
“…Storage of roots at <12°C results in chilling injury (Picha 1987). Roots can also be stored under controlled atmosphere conditions (Mcconnell et al 2005). Uncured roots decayed rapidly when stored at low O 2 tensions but, after curing, O 2 tensions of 2 and 4% did not appear to be harmful (Delate and Brecht 1989).…”
Section: Storage Methodsmentioning
confidence: 98%
“…B-carotene content of fresh-cut sweet potatoes at the end of storage had an average of 6.01 mg per 100 g of FW (Erturk and Picha 2007 ). McConnell et al ( 2005 ) packed shredded sweet potatoes from two major commercial cultivars ('Beauregard' and 'Hernandez') in low (PD-900) and medium (PD-961) O 2 permeability bags at 4 °C and fl ushed them with gas composed of 5 % O 2 and 4 % CO 2 . Samples from 'Beauregard' and 'Hernandez' cultivars stored under MAP did not undergo any change in ascorbic acid contents (15.4 and 14.7 mg/100 g, respectively).…”
Section: Sweet Potatomentioning
confidence: 99%